Synthesis and Characterisation of Cobalt(II) Complexes of 3-Hydroxyflavone - Yang, Farina; D. A., Rice (Universiti Putra Malaysia Press, 1995)
The syn theses of diaquabis (3-hydroxyflavonato) cobalt(II) and bis(pyridine) bis (3hydroxyflavonato) cobalt(II) are described. Results from infrared spectra clearly show that the 3-hydroxyflavonato anion forms a chelate through the 3-hydroxy 4-keto groups. The electronic spectra of both complexes indicate that cobalt(II) has an octahedral geometry. Quantitative analyses of the isolated products gave good agreement with calculated values. Magnetic moment measurements show that both compounds are high spin £ cobalt(II) complexes. The powder diffraction pattern of the pyridine adduct gave almost 1:1 correspondence with tTans-bis (pyridine) bis (3-hydroxyflavonato) nickel (II) which has an octahedral geometry. Therefore, it is highly likely that bis(pyridine)bis(3hydroxyflavonato) cobalt(II) is octahedrally co-ordinated with two chelating 3-hydroxyflavonato anions and two pyridine molecules occupying tTans positions.